Half-a-century (1971-2020) of glacier shrinkage and climatic variability in the Bhaga basin, western Himalaya - Das, Suresh; Sharma, Milap Chand; Murari, Madhav Krishna; Nüsser, Marcus; Schmidt, Susanne (Journal of mountain science, 2023)
Glacier shrinkage is a globally occurring phenomena. High-resolution change detection based on frequent mapping and monitoring of high-altitude glaciers is necessary to precisely evaluate future water availability and to understand glacier evolution under different climatic scenarios in the Hindukush-Karakoram-Himalayan (HKH) region. This also holds true for the Bhaga basin of the western Himalaya. This study investigates glacier and glacier lake changes in the Bhaga basin, over the last five decades based on satellite imagery including Corona KH4 (1971), Landsat 7 Enhanced Thematic Mapper Plus (ETM+; 2000), Linear Imaging Self-Scanning Sensor (LISS IV; 2013), and Sentinel 2 (2020). Regional temperature and precipitation trends were evaluated from gridded climatic datasets (1900-2020). In the Bhaga basin 306 glaciers (>0.2 km2) were mapped with a total area of 360.3 ± 4.0 km2, of which 55.7 ± 0.6 km2 was covered with debris in 2013. The total glacier covered area decreased by ∼8.2 ± 1.5 % (0.16 ± 0.03 % yr−1) during the entire observation period 1971-2020, with noticeable heterogeneity between tributary watersheds. In the past two decades (2000-2020), the deglaciation rate has increased significantly (0.25 % yr−1) compared to the previous decades (1971-2000; 0.12 % yr−1). Glacier lake area increased by 0.6 ± 0.1 km2 (0.012 km2 yr−1) between 1971 and 2020. The NCEP/NCAR climatic data reveals an increase of 0.63°C in temperature and a decrease of 6.39 mm in precipitation for the period 1948-2018. In comparison, APHRODITE data shows an increasing trend in temperature of 1.14°C between 1961 and 2015 and decreasing trend in precipitation of 31 mm between 1951 and 2007. Both NCEP/NCAR and APHRODITE data reveal significant temperature increase and precipitation decrease since the 1990s, which have probably augmented ice loss in the Bhaga basin during the early 21st century.
Gesehen am 29.03.2023